2023
DOI: 10.1159/000528315
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Ketamine and Lamotrigine on Cognition: Emotion Interaction in the Brain

Abstract: <b><i>Introduction:</i></b> Cognition and emotion are fundamentally integrated in the brain and mutually contribute to behavior. The relation between working memory (WM) and emotion is particularly suited to investigate cognition-emotion interaction since WM is an essential component of many higher cognitive functions. Ketamine affects not only WM but also has a profound impact on emotional processing. Effects of acute ketamine challenge are sensitive to modulation by pretreatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Both, the PK and LK groups had increased scores on the DSS scale and on the subscales of the 5D-ASC questionnaire. Detailed behavioral and demographic results are provided in Supplementary Table 1 and in our previous publication [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both, the PK and LK groups had increased scores on the DSS scale and on the subscales of the 5D-ASC questionnaire. Detailed behavioral and demographic results are provided in Supplementary Table 1 and in our previous publication [28].…”
Section: Resultsmentioning
confidence: 99%
“…Expected effect sizes were based on previous reports [39]. More details about the design and procedures are provided by Gärtner et al [28].…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…We used PDC (a glutamate transporter inhibitor, known to increase synaptic glutamate by inhibiting the uptake of glutamate) and lamotrigine (inhibits glutamate release). Lamotrigine is a broad-spectrum anticonvulsant and its downstream effects on neuronal function include inhibition of glutamate release (Bacher and Zornow, 1997; Anand et al ., 2000; Makatsori et al ., 2004; Large et al ., 2005; Gärtner et al ., 2023) by inhibiting voltage-sensitive sodium channels (Messenheimer, 1995). We found that the stimulation of glutamatergic neurons in LHb via local infusion of PDC resulted in a significant reduction in TH-ir and consequently CPP score.…”
Section: Discussionmentioning
confidence: 99%